Risk Assessment of Coronavirus Disease (COVID-19) Transmission among Physicians Working at a COVID-dedicated Tertiary-care Hospital (Mugda Medical College Journal, 2023)
Background and aims: In the earlier stage of pandemic, a sizeable number of physicians and other healthcare workers were infected with SARS-CoV-2. The aim of this study was to assess the factors associated with the risk of SARS-CoV-2 infection among physicians working at a COVID-dedicated tertiary care hospital, within and outside the medical workplace.Methods: This case control study was conducted among the physicians and surgeons working at different departments of Mugda Medical College and Hospital and undergone different pattern of exposure to COVID patients within the period of 20 April, 2020 and 20 July, 2020. Respondents were queried regarding job description, workplace exposures, respiratory protection, hospital policy of disease prevention, and extra-occupational activities during duty period. Chi-square test was done and odds ratios for physicians’ infection were calculated. A p-value